Rethinking Poverty Reduction: The Role of HDI Components and Labor Force Participation in Semarang - Sanjoko, Deny Cahyadinanto; Yusuf, Maulana Ghani (Kirana Publisher (KNPub), 2025)
This study investigates the influence of the Human Development Index (HDI) and its components—life expectancy and per capita expenditure—along with the labor force participation rate (LFPR), on poverty in Semarang City using time series data from 2010 to 2024. Two regression models were tested: Model 1 used HDI and LFPR, while Model 2 used life expectancy, per capita expenditure, and LFPR. The results show that per capita expenditure significantly reduces poverty, while life expectancy shows a positive and significant effect. HDI also has a negative and significant effect in the aggregate model. LFPR is not statistically significant in either model. Both models passed classical assumption tests, and Model 2 showed higher explanatory power than Model 1. These findings highlight the importance of income in poverty reduction and suggest further research into the demographic dimensions of poverty. Comparative modeling is recommended for broader policy insights.